Impact of the precise ephemeris on accuracy of GNSS baseline in relative positioning technique - Tran, Dinh Trong; Nguyen, Dinh Huy; Luong, Ngoc Dung; Dao, Duy Toan (Vietnam Journal of Earth Sciences, 2020)
For advanced geodesy tasks that require high-accuracy, such as tectonics, surveying services usually use not only long-baselines but also the duration of tracking GNSS satellites in a long (e.g., 24/7). The accuracy of these baselines in baseline analysis is dominated by inaccuracy satellite positioning and orbit, leading to specified accuracy may not be adequate. One way to overcome this problem is to use the final precise ephemeris, provided by IGS. The objective of this study is to investigate the impact of precise ephemeris on the accuracy of GNSS baselines in relative positioning techniques in two aspects: baseline length and duration of tracking GNSS satellites. To this end, 197 baselines were generated from a total of 88 CORS stations in South Korea, and then thirteen testing cases were constructed by grouping baseline lengths from under 10 km to over 150 km. Besides, data for one day of each CORS was divided into the different duration, such as 1, 2, 3, 6, and 24 hours. The GNSS measurements have been processed by TBC software with an application of the broadcast and precise ephemerides. The precision of the baseline processing from two types of ephemeris was analyzed about baseline lengths and time of data. The obtained results showed that using precise ephemeris significantly improved the accuracy of baseline solutions when the length of the baseline larger than 50km. In addition, this accuracy is independent of the length of baselines in the case of the precise ephemeris. Finally, the result of the testing baselines was enhanced when the duration of tracking data increases.